Agrarian Culture and Javanese Attachment to Their Land: A Study of Local Wisdom Values in Javanese Proverbs - Dwi Wulan Pujiriyani (MOZAIK HUMANIORA, 2020)
Agrarian culture is closely related to the scope of the relationship between humans and their agricultural land. This study aims to analyze the values of Javanese attachment to their land. This research was conducted using qualitative methods through proverbial analysis. Proverb analysis was done through the method of classifying or grouping keywords from 134 proverbs. The results show that Javanese attachment to their land can be found in two main dimensions, namely land as a source of income or land economy and landrootedness. In Javanese culture, it turns out that proverbs which contain the obligation to protect the land are stronger than proverbs that contain the right to make decisions on land. This indicates that culturally, the value of protecting the land is very important for Javanese people. Sanctions from the universe and the creator are strongly implied for them who negligent to maintain their land properly.